Teknologi Pirolisis Pembuatan Asap Cair dari Sekam Padi - Alieftiyani Paramita Gobel; A Taufik Arief (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
The production and use of liquid smoke from rice husks among the farming community in Belitang sub-district is still very limited and not many people even know about liquid smoke and its benefits. During the rice husk is made of charcoal and used for mixing the soil as an additional nutrient to the soil. Seeing these conditions, the aim of carrying out community service activities is to increase public knowledge of the potential of rice husk in the form of liquid smoke which can be used as an organic pesticide. The activity method is carried out in several steps, namely socialization, the process of making and assembling tools and the practice of making smoke by the community on a small scale. Designed pyrolysator equipment portable consisting of combustion chamber tubes, smoke cooling chamber tubes and smoke flow pipes which are used to produce liquid smoke. The rice husk burning process was carried out using a pyrolysis scheme within 6 hours and produced 90 ml of black liquid smoke with little oil content. This indicates that the liquid smoke produced is of low quality. The result of this Community Service Program (PPM) activity is that the community understands and understands the use of liquid smoke and the process of making liquid smoke.